2018
DOI: 10.1016/j.jacc.2018.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapy for Heart Failure With Reduced Ejection Fraction

Abstract: In this contemporary outpatient HFrEF registry, significant gaps in use and dose of guideline-directed medical therapy remain. Multiple clinical factors were associated with medication use and dose prescribed. Strategies to improve guideline-directed use of HFrEF medications remain urgently needed, and these findings may inform targeted approaches to optimize outpatient medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
723
9
21

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 931 publications
(818 citation statements)
references
References 20 publications
65
723
9
21
Order By: Relevance
“…Consistent with this, the majority (58%) of patients enrolled in DAPA‐HF did not have known diabetes. The proportion with an existing diagnosis of diabetes (42%) was similar to that in contemporary registries but somewhat larger than in the comparator HFrEF trials . The patients randomized in DAPA‐HF were also broadly similar, in other respects, to those in the recent registries, although, as has been recognized previously, atrial fibrillation was less frequent in Asian patients .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Consistent with this, the majority (58%) of patients enrolled in DAPA‐HF did not have known diabetes. The proportion with an existing diagnosis of diabetes (42%) was similar to that in contemporary registries but somewhat larger than in the comparator HFrEF trials . The patients randomized in DAPA‐HF were also broadly similar, in other respects, to those in the recent registries, although, as has been recognized previously, atrial fibrillation was less frequent in Asian patients .…”
Section: Discussionsupporting
confidence: 70%
“…Three recent registries encompassing Europe, Asia and the United States of America (USA) were used for comparison of patients in DAPA‐HF with the so‐called ‘real‐world’ cohorts …”
Section: Methodsmentioning
confidence: 99%
“…The finding that 62% of the patients up‐titrated to 49/51 or 97/103 mg bid of sacubitril/valsartan are relevant when compared to registry data, showing only 43% of patients receiving more than 24/26 mg bid of sacubitril/valsartan in an outpatient setting . This gap between data from controlled trials and daily practice requires further study, and gives room for future improvement in HF therapy .…”
Section: Discussionmentioning
confidence: 96%
“…Several large cohorts and trials have reported dose, including a Swedish multicentre cohort (n = 2093) 33 ; the BIOSTAT-CHF Optimal dosing of medication in acute heart failure study (n = 2100) 16 ; the ESC-HF, 6 CHAMP-HF, 8 CHECK-HF, 31 and PINNACLE (n = 1421) 34 registries; and the GUIDE-IT trial. 35 The proportions prescribed ≥50% and target dose for each class are ACE-I/ARB 40% to 76% for ≥50% and 14% to 44% target; beta-blockers 31% to 55% for ≥50% and 6% to 28% target; and MRA 49% to 98% for ≥50% and 31% to 77% target.…”
Section: Target Dosingmentioning
confidence: 99%
“…[1][2][3] Assessment of appropriate use requires patient-level knowledge of indications, contraindications, and tolerability. [6][7][8] Maximum tolerated doses were utilized in the landmark clinical trials, are recommended in guidelines, 1-3 and associated with improved outcomes but not excess discontinuation rates. [6][7][8] Maximum tolerated doses were utilized in the landmark clinical trials, are recommended in guidelines, 1-3 and associated with improved outcomes but not excess discontinuation rates.…”
Section: Introductionmentioning
confidence: 99%